Fighting Corruption in East Asia : Solutions from the Private Sector - Arvis, Jean-Francois; Berenbeim, Ronald E. (Washington, DC: World Bank, 2013)
The critical need for private sector involvement in the fight against corruption is now an accepted fact, particularly in East Asia, where there is a buoyant private sector and where corruption has often been equated with cronyism. Cutting off corruption's supply side is a vital step in limiting the economic damage inflicted by corrupt practices. Despite the importance of private sector efforts in this regard, little attention has been paid to company anticorruption programs and to trying to learn from company experience. This book, which is based on research cosponsored by the World Bank and the Conference Board, provides detailed documentation of the efforts of Western and Asian companies to develop good standards of business conduct in their East Asian operations. It provides evidence that a common set of principles for resisting corruption can be established notwithstanding the rich cultural diversity and ownership structure of firms based in that region.